Sistema de control de inventarios de paquetes especiales en el área de Copacking de la empresa Solupack S.A - Chilig Velásquez, Yesenia Katherine (2022)
For companies, inventory management and control are very beneficial in today's business world, as they are a vital part of the intense competition in the industry. The design of an inventory control system for the copacking area of the company Solupack S.A., is of vital importance since it is required that the organization operates at optimal financial levels and that the products meet the needs and expectations of customers. So, a study was carried out with a qualitative approach, with the application of deductive and inductive methods. The techniques applied were participant observation and interviews with the participants of the copacking area, in an informal, semi-structured and open way, whose census-type sample was established for a total of 17 workers. Research of the current situation of the company was carried out, which allowed identifying the main causes that may be affecting the copacking area of the company. Subsequently, the inventory control processes were defined; the purchase planning and management planning process was identified; it was defined how the reception and storage will be carried out (merchandise segmentation by ABC classification); it was determined how the inventory control will be carried out. The process of delivering products to customers was established, and then the inventory management indicators for the copacking area were developed. Finally, a proposal for an action plan was developed so that the managers can know and determine the feasibility of implementing this project in the company Solupack S.A.